2011
DOI: 10.1186/1471-2334-11-172
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors associated with dengue fever in a central highlands Province, Vietnam

Abstract: BackgroundDengue is a leading cause of severe illness and hospitalization in Vietnam. This study sought to elucidate the linkage between climate factors, mosquito indices and dengue incidence.MethodsMonthly data on dengue cases and mosquito larval indices were ascertained between 2004 and 2008 in the Dak Lak province (Vietnam). Temperature, sunshine, rainfall and humidity were also recorded as monthly averages. The association between these ecological factors and dengue was assessed by the Poisson regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
98
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 21 publications
21
98
1
3
Order By: Relevance
“…These results are also consistent with those of the studies conducted in other tropical/sub-tropical environments. For example, some studies in Vietnam found that dengue was most prevalent in the wet season (Cuong, 2011, Pham et al, 2011, Toan, 2013. C= Cluster (n) = number of SLAs; *= Primary cluster; Sec = Secondary cluster; R= Radius; O=Observed cases; E=Expected cases; RR=Relative risk; LLR= Log-likelihood ratio Table 4: Space-time clusters of dengue identified using spatial scan test statistic…”
Section: Discussionmentioning
confidence: 99%
“…These results are also consistent with those of the studies conducted in other tropical/sub-tropical environments. For example, some studies in Vietnam found that dengue was most prevalent in the wet season (Cuong, 2011, Pham et al, 2011, Toan, 2013. C= Cluster (n) = number of SLAs; *= Primary cluster; Sec = Secondary cluster; R= Radius; O=Observed cases; E=Expected cases; RR=Relative risk; LLR= Log-likelihood ratio Table 4: Space-time clusters of dengue identified using spatial scan test statistic…”
Section: Discussionmentioning
confidence: 99%
“…Numerous mathematical models have been designed and used to assess the impact of climate change and seasonality on the transmission dynamics of mosquito-borne diseases, such as malaria (Agusto et al 2015;Ebi et al 2005;Jaenisch and Patz 2002;Mordecai et al 2012;Paaijmans et al 2009), dengue (Chen et al 2010;Hales et al 2002;Pham et al 2011;Wu et al 2009;Yang et al 2011), chikungunya (Fischer et al 2013;Meason and Paterson 2014) and WNv (Abdelrazec et al 2015;Wang et al 2011). For instance, such models allow for the determination of parameters, or variables, that influences the life-cycle of the mosquitoes (Ahumada et al 2004;Cailly et al 2012;Tran et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also exist that the seasonal abundance of dengue vectors are positively correlated with the seasonality of dengue fever activity [18,19] . Besides temperature and humidity [20] , precipitations have been reported influential to dengue vectors' distribution and abundance [21,22] .…”
Section: Introductionmentioning
confidence: 99%